Do UK Real Estate SMEs' Board Characteristics Affect Accrual-Based and Real Activities-Based Earnings Management? - CHAO, RUIXI (2020)
This study surveyed the connection between board characteristics and accrual-based earnings management (AEM) and real activities-based earnings management (RAEM) in UK real estate small and medium-sized enterprises (SMEs). From 2016 to 2018, a total of 144 annual observations of real estate SMEs from the UK FTSE 350 were sampled. The capture of AEM uses the traditional Jones model (1991), and three separate components of RAEM proposed by Roychowdhury (2006) and Kim and Park's (2014) comprehensive RAEM indicator were applied to determine the level of earnings management (i.e., the dependent variable). The independent variables are these SMEs' board characteristics: board size, board non-executive directors (NEDs), board meetings, board gender diversity and CEO duality. Then, performing Stata software to obtain descriptive statistics, Pearson correlation and regression analysis on the collected data, which constructs a linear regression model of board characteristics and earnings management.